Pelaksanaan Pembelajaran Fiqih Melalui Kitab Nadom Fiqih Junior (Karya Achmad Kamaludin) Pada Santri Taman Pendidikan Al-Qur’an Mamba’ul Falah Bondowoso - Syaiful Rizal (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2020)
ABSTRAK The Indonesian community (urban and rural) now appears a variety of various practical methods or special methods to achieve effective and efficient targets. In order to realize the learning atmosphere and the learning process by supporting the development of students. One of the basic practical jurisprudence learning methods that can be used for students is the Memorizing Method of the Nadlom Fiqh Junior Book. Nadlom Fiqh Book is a book of fiqh in the style of Nadlom which is a practical method of understanding the science of jurisprudence according to the tendency of students and society today, who like everything practical, including consuming reading material. The purpose of this study was to find out how the planning, implementation and evaluation of fiqh learning through the junior fiqh nadlom book (The Work of Achmad Kamaludin) on Santri Al-Qur'an Education Park Mamba'ul Falah Bondowoso. This study uses a phenomenological qualitative approach. The technique of determining the informants used purposive sampling. The technique of data collection uses observation, interviews and documentation. Data analysis uses the method proposed by Miles and Huberman, namely; data reduction, data display, drawing conclusions or verification. The validity of the data uses source triangulation. The results showed that the program method of memorizing the nadhom fiqih junior book could facilitate the ability of TPQ students in the realm of basic fiqh learning related to the Ubudiyah of santri. This is not excluded from the preparation, implementation and evaluation of learning that is always well prepared by the asatidz. To support the success of the program, the TPQ assisted by the foundation made every effort to fulfill facilities and infrastructure for those who could support and succeed the program. So the program provides a new nuance for TPQ which usually only focuses on the learning process of the Qur'an without optimizing fiqh learning. Keywords: Memory Method, Nadlom Fiqh Book, Al-Qur'an Educational Park